The Evaluation of Waste Papers for the Ceramic industry - Selte, Aydin; Guler, Kerem Altug; Marsoglu, Muzeyyen (CARL HANSER VERLAG, 2012)
The aim of this study is the production of the metal tile core using waste paper. Paper which can be recycled many times is one of the most consumed materials in Turkey and all around the world. The reason behind the preference of paper usage is that 80 % of waste paper can be recycled. It has been noticed that recycled paper can be used in ceramic industry, as for instance for roof coverings and tiles, as a low cost raw material. A certain amount of waste paper was soaked with water and turned into pulp followed by a forging process to form the pulp into fibres. The mixture used as raw material for metal tile core production was composed of clay, quartz, and pulp. The raw material was shaped into tiles by slip casting and hand pressing. Tiles were dried, in a drying oven and coated with epoxy resin. Water absorption and bending tests were applied to the final samples.
Keywords: CEMENT RAW-MATERIAL; Materials Science